2011
DOI: 10.1088/0031-9155/56/18/008
|View full text |Cite
|
Sign up to set email alerts
|

Improved contrast deep optoacoustic imaging using displacement-compensated averaging: breast tumour phantom studies

Abstract: For real-time optoacoustic (OA) imaging of the human body, a linear array transducer and reflection mode optical irradiation is usually preferred. Such a setup, however, results in significant image background, which prevents imaging structures at the ultimate depth determined by the light distribution and the signal noise level. Therefore, we previously proposed a method for image background reduction, based on displacement-compensated averaging (DCA) of image series obtained when the tissue sample under inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…One of the reasons is that compressive deformation is more likely to result in out-of-plane motion at slippery interfaces between e.g., muscle epimysia, or between glands and surrounding tissue. The other reason is that echo clutter tends to move at a similar speed as true signals in compression mode, whereas the displacement rate is roughly half the displacement rate of true signals in shear mode [29]. Therefore shear deformation will allow for more efficient separation between true signal and echo clutter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the reasons is that compressive deformation is more likely to result in out-of-plane motion at slippery interfaces between e.g., muscle epimysia, or between glands and surrounding tissue. The other reason is that echo clutter tends to move at a similar speed as true signals in compression mode, whereas the displacement rate is roughly half the displacement rate of true signals in shear mode [29]. Therefore shear deformation will allow for more efficient separation between true signal and echo clutter.…”
Section: Discussionmentioning
confidence: 99%
“…In combined OA and US imaging, motion tracking of US images provides the knowledge of local tissue displacement that is required for OA deformation compensation. In-vitro tissue [28] and gelatin phantom [29] studies, having realistic echogenicity in addition to the optical properties, have consistently shown that DCA significantly improves imaging depth in comparison to conventional averaging without probe motion. These experiments were performed with controlled probe motion using motorized stages.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…% phantoms with 2 mg∕mL of methylparaben added as a preservative. 42 The gelatin phantom matrix was enriched with scattering and absorbing properties produced by titanium dioxide powder (KAI Tech Labs) and a suspension of gold nanorods (GNRs) made in our laboratory. At the laser wavelength of 805 nm, GNRs, homogeneously distributed in the phantoms, provided optical absorbance μ a ≈ 0.2 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The perfect overlap of PA and US images is essential for being able to take advantage of the complementary contrast mechanisms. Moreover, this also allows for using US imaging information for improvements of the PA image, such as in displacement compensated averaging [6]. Hybrid PA/US imaging devices have also been demonstrated for intravascular imaging, using an imaging catheter [7].…”
Section: Introductionmentioning
confidence: 99%